MODELS AND ALGORITHMS FOR IDENTIFYING RELATIONSHIPS IN TUNNEL TRAFFIC - Клюшник, Віталій; Чернецький, Євген (SWorldJournal, 2026)
The article considers the problem of identifying applications in tunnel traffic in conditions of widespread use of encryption, VPN technologies, and anonymous networks. An identification model based on hidden Markov models is proposed, which uses statisti